ASSA14-03-14 Mitochondrial DNA damage contribute to ischemia/reperfusion-injury in rat cardiac myocytes: the protective effects of lycopene. (1st December 2014) - Yue, R; Wang, WE; Xia, X; Jiang, J; Yang, D; Han, Y; Zeng, C
Abstract : Objectives: Recent studies suggest that oxidative stress and mitochondrial dysfunction are involved in the pathogenesis of ischemia/reperfusion (I/R)-injury. Mitochondrial DNA (mtDNA) is highly vulnerable to oxidative stress and lycopene is found to protect mtDNA against oxidative damage. Our recent study indicates lycopene reduced I/R-injury in vitro by alleviating oxidative stress and preventing mitochondrial dysfunction. This study was aimed to determine whether mtDNA damage is involved in the I/R-injury and whether lycopene can protect cardiac myocytes from I/R-injury by inhibiting mtDNA damage. Methods: We established I/R-injury model with rat in vivo and we also established hypoxia/ reoxygenation-injury model with H9c2 cells to simulate I/R-injury in vitro . Reactive oxygen species (ROS) and mitochondrial superoxide levels were determined. Mitochondrial 8-hydroxyguanine (8-OHdG), mtDNA content and mtDNA transcript levels were detected to find out if mtDNA were damaged; The protein expression of mitochondrial transcription factor A (Tfam) in mitochondrial, a key protein for mtDNA transcription, replication and component for nucleoid organisation were also determined by western blot. Results: I/R significantly increased reactive oxygen species (ROS) production and mitochondrial superoxide levels. In addition, I/R increased mitochondrial 8-hydroxyguanine (8-OHdG) content, while reduced mtDNA content and mtDNA transcript levels. Consistent with these findings, I/R was found to decrease the protein expression of Tfam in mitochondrial. Lycopene pretreatment efficiently attenuated the oxidative damage to mtDNA induced by I/R both in vivo and in vitro . Conclusion: Our results suggest that mtDNA damage may account for I/R-injury. Lycopene has a great pharmacological potential in protecting mtDNA against the I/R-injury in the heart.